The Boston directory containing the city record, a directory of the citizens, and business directory : for the year commencing July 1, 1885. - Sampson, Murdock, & Co. (Tufts Archival Research Center, 2005)
This version contains a full text transcription of the A-Z personal directory and images of advertisements included in the original printed edition.